THE NECESSITY OF THE NEW RISE OF THE ECO ETHIC - DONEV, Dejan (Studia Universitatis Babeş-Bolyai Bioethica, 2016)
Modern civilization is in crisis. The gaps are numerous and deep! Along with new and great scientific discoveries, the humanity at the same time isn't increased. This led us to moral disorientation in various areas of life. In the late 60s and early 70s of the last century, the first premonitory signs of this development showed especially encouraged by the threat of environmental pollution. Human unlimited development showed the first negative impact on the world we live in, the nature that surrounds us. The modern man becomes more aware of fact that it can destroy the flying boat, the house in which he lives. The text deals with the increased need for answering two basic questions according to the new area of research in ethics, i.e. human behavior towards nature. The first question is do we need indeed, for resolving this problem, a scientific strategy postulated on the basics of ecology as a science of the environment and transformed into social and political decision (as biopolitics on an international and national level) or do we need a new ethics for the environment that will be established as a scientific strategy and therefore as a biopolitics? The second issue concerns whether the nature and environmental protection are interesting for us only on an instrumental level or we believe that nature has intrinsic value, so it can exist even without man? Necesitatea apariției unei noi eco-etici. Civilizația modernă este în criză. Lacunele sunt numeroase și profunde! Impreună cu noile și marile descoperiri științifice, omenirea, în același timp, nu s-a elevat. Acest lucru ne-a condus la o dezorientare morală în diverse domenii ale vieții. În pe sfârșitul anilor 60 și începutul anilor 70 ai secolului trecut, primele semne premonitorii ale acestei evoluții s-au dovedit încurajate, în special, de amenințarea poluării mediului. Dezvoltarea umană nelimitată dovedește un prim impact negativ asupra lumii în care trăim, natura care ne înconjoară. Omul modern devine mai conștient de faptul că poate distruge barca plutitoare, casa în care trăiește. Textul tratează nevoia crescută de a răspunde la două întrebări de bază în acord cu noua arie de cercetare etică, i.e. comportamentul uman în raport cu natura. Prima întrebare este – avem noi într-adevăr, pentru rezolvarea acestei probleme, o strategie științifică postulată pe elementele fundamentale ale ecologiei ca știință a mediului și transformată în decizie socială și politică (ca biopolitici la nivel internațional și național), sau avem nevoie de o nouă etică pentru mediu care va fi stabilită ca o strategie științifică și, prin urmare, ca biopolitici? Al doilea aspect este de a ști dacă natura și protecția mediului sunt interesante pentru noi doar la nivel instrumental sau noi credem că natura are o valoare intrinsecă, deci poate exista chiar și fără om? Cuvinte-cheie: eco-etică, natură, mediu, ecologie.